A Digest of the Laws and Ordinances for the Government of the Municipal Corporation of the City of Reading, Pennsylvania, Park Rules and Regulations, at 240, City Park, § 20(8) (1897) - (:unkn) unknown (General Publisher, 1897)
Prohibited any person from carrying firearms, or discharge in the common or within fifty yards therof, or throw stones or other missiles therein.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES